2012
DOI: 10.1016/j.neuroscience.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine-induced neurotoxicity linked to ubiquitin-proteasome system dysfunction and autophagy-related changes that can be modulated by protein kinase C delta in dopaminergic neuronal cells

Abstract: A compromised protein degradation machinery has been implicated in methamphetamine (MA)-induced neurodegeneration. However, the signaling mechanisms that induce autophagy and UPS dysfunction are not well understood. The present study investigates the contributions of PKC delta (PKCδ) mediated signaling events in MA-induced autophagy, UPS dysfunction and cell death. Using an in vitro mesencephalic dopaminergic cell culture model, we demonstrate that MA-induced early induction of autophagy is associated with red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 74 publications
1
50
0
Order By: Relevance
“…28 The cellular and molecular mechanism(s) leading to astrogliosis mediated by diverse agents as well as the related neuroinflammatory pathways that trigger astrogliosis are still areas of active investigation. While the role of drugs of abuse, such as morphine and methamphetamine, on induction of apoptosis, HIV disease progression, neuronal injury and neurodegeneration has been well established, [34][35][36][37][38][39] information in how the drugs influences astrogliosis and the role of autophagy in this process is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…28 The cellular and molecular mechanism(s) leading to astrogliosis mediated by diverse agents as well as the related neuroinflammatory pathways that trigger astrogliosis are still areas of active investigation. While the role of drugs of abuse, such as morphine and methamphetamine, on induction of apoptosis, HIV disease progression, neuronal injury and neurodegeneration has been well established, [34][35][36][37][38][39] information in how the drugs influences astrogliosis and the role of autophagy in this process is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we recently demonstrated that methamphetamine (MA) induced dopaminergic neurotoxicity may be linked to concomitant impairment in mitochondrial function and autophagic flux (Kanthasamy et al, 2006; Lin et al, 2012). Additionally, recent reports implicate aberrant activation of c-Abl in the impaired autophagic clearance of α-synuclein and subsequent induction of dopaminergic neurotoxicity (Hebron et al, 2013a, b).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that protein kinase Cδ (PKCδ) is an oxidative stress-sensitive, pro-apoptotic kinase, which plays a causal role in apoptotic neuronal cell death. [12][13][14][15] We demonstrated that phosphorylation of tyrosine residue 311 and caspase-3-dependent proteolytic cleavage result in a persistent increase in the kinase activity, which promotes neuronal apoptosis. 13 Herein, we evaluate the role of PKCδ in prion neurotoxicity in ex vivo brain slice culture and in vivo experimental models of infectious prion disease.…”
Section: Introductionmentioning
confidence: 88%